Manfaat Strategi Algoritma Pemrograman dalam Kurikulum Merdeka - Sri Astutik; Ayuk Witria Ningsih; Putri Anjani (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2024)
Education in the digital era requires strong integration of computer programming in the educational curriculum. Programming algorithms are the main key in developing critical thinking and problem solving skills among students. The Merdeka Curriculum reinforces the importance of teaching programming algorithms as part of a curriculum that is flexible and adaptive to meet future demands. This research explores the benefits of programming algorithm strategies in the Merdeka Curriculum, including improving students' analytical, logical and systematic abilities, as well as their preparation for challenges in the digital era.